Purification of Factor IX or its Precursor Isolation of a Hageman-PTA Fraction - Yin, E. T; Duckert, F (Thrombosis and Haemostasis, 1961)
A purification method is described which allows the isolation of two active fractions: Hageman factor — PTA fraction and factor IX or IX precursor fraction. These two fractions are characterized and some of their properties are indicated.